Unraveling Lithium Plating and SEI Properties during Fast Charging of Li-Ion Batteries - Luo, Mei; Gao, Xiang; Mijailovic, Aleksandar S; Wang, Guanyi; Jansen, Andrew N.; Yang, Zhenzhen; Wu, Qingliu; Sheldon, Brian W.; Xu, Jun; Lu, Wenquan (Meeting abstracts (Electrochemical Society), 2024)
As the electric vehicles market expands rapidly, the need for fast-charging lithium-ion batteries become increasingly imperative. However, the persistence of lithium plating, particularly on graphite negative electrodes in state-of-the-art lithium-ion batteries (LIBs), continues to pose performance degradation and safety hazards. Understanding the dominant limitation mechanism remains a subject of controversy. To evaluate the dominant role among particle-level diffusion and charge-transfer at the electrode interphase, we utilized ultra-thin electrodes with different-size graphite particles in conjunction with a pseudo-2-dimensional (P2D) model to evaluate the most likely plating mechanism. The superior performance of small graphite particles, coupled with well-matched modeling data, indicated that particle-level diffusion is the primary mechanism contributing to plating at high rates. Furthermore, we investigated how fast-charging rates influence the morphology of lithium dendrites and their solid electrolyte interphase (SEI) properties using 1.6 Ah pouch cells featuring a LiNi 0.5 Mn 0.3 Co 0.2 O 2 cathode and graphite anode provided by Nanoramic Laboratories. Our investigation involved a comparative analysis of the aging behavior of NMC/Gr cells subjected to various charging rates — 0.5C, 2C, 4C, and 6C. Through a series of post-mortem characterizations, including electrochemical impedance spectroscopy (EIS), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDS), we identified distinct dendrite morphologies at the graphite anode under varying charging rates, along with fluorine-richer SEI for faster charging process. These findings provide a comprehensive understanding of lithium plating mechanisms, offering valuable insights into the fast-charging behavior in practical Li-ion battery applications. Acknowledgement This material is based upon work supported by the U. S. Department of Energy’s Office of Energy Efficiency and Renewable Energy (EERE) under the Advanced Manufacturing Office, award number DE-EE0009111. This work was mainly conducted at the Cell Analysis, Modeling, and Prototyping Facility at Argonne National Laboratory. We used resources of the Center for Nanoscale Materials, U.S. Department of Energy (DOE) Office of Science User Facilities operated for the DOE Office of Science by Argonne National Laboratory under Contract DE-AC02-06CH11357.